European guidelines for validating non-formal and informal learning - (:unkn) unknown (Office for Official Publications of the European Communities, 2009)
"Validating non-formal and informal learning is increasingly seen as a way of improving lifelong and lifewide learning. More European countries are emphasising the importance of making visible and valuing learning that takes place outside formal education and training institutions, for example at work, in leisure time activities and at home. The guidelines presented in this publication aim to support this process by identifying the main challenges facing policy-makers and practitioners and - to a certain degree - pointing to possible ways to respond. They should be seen as a practical tool, providing expert advice to be applied on a purely voluntary basis. Their impact relies exclusively on their relevance and ability to add value at national or local levels." (Hrsg., BIBB-Doku)
Keywords: L 2.1.1 Informelles Lernen; L 2.1.3 Erfahrungslernen; S 2.2.4.4 Anerkennung non-formaler Qualifikationen; I 2.2 Europa; Informelles Lernen; Erfahrungswissen; Anerkennung; Europa